Association of anticardiolipin antibodies with epilepsy in children - Shiva, Shadi; Khanzadeh, Shokoufeh; Rashidi, Farzad; Lucke-Wold, Brandon (Trends in Immunotherapy, 2023)
We investigated the association of anticardiolipin antibodies (aCL) with epilepsy development and characteristics in children. This prospective case-control study included 40 epileptic children and 40 sex- and age-matched controls. Epileptic children had higher levels of aCL compared to healthy controls (5.66 ± 5.41 versus 2.37 ± 2.28; p value = 0.001). The novel finding of elevated levels of aCL predicted response to IVIg therapy (p value = 0.009). Patients with normal EEG had lower levels of aCL compared to those with EEG abnormal findings (p value = 0.015). Patients with the combined type of epilepsy had statistically significant higher levels of aCL compared to other types (p value = 0.046). Also, aCL levels were correlated with seizure frequency (p value = 0.019). These results declare the possible involvement of such antibodies in the onset or pathogenesis of epilepsy. Screening for aCL may help in the timely diagnosis of epilepsy and initiation of appropriate treatment.